2015
DOI: 10.1016/j.applanim.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for litter differences in play behaviour in pre-weaned pigs

Abstract: HighlightsFirst demonstration of between litter differences in play behaviour in pigs.Litter differences in play behaviour appear independent of overall activity levels.Litter differences in play behaviour associate strongly with post-natal growth.Pre-natal factors (particularly birth weight and BMI) associate positively with play behaviour.Pre-weaning play behaviour has potential as an indicator of positive welfare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 42 publications
12
41
0
Order By: Relevance
“…Paradoxically, activation of ERK1/2, which also is upregulated by insulin (Gosmanov et al 2002) and promotes mTOR activity and protein synthesis in skeletal muscle (Mccubrey et al 2011), was augmented in LD and gastrocnemius between day 9 and 21 across all groups. Although speculative, this effect may be a consequence of the developmental increase in postprandial insulin levels observed in the study (data not shown), as well as an increase in muscle activity (Gosmanov et al 2002) associated with piglet growth (Brown et al 2015). …”
Section: Discussionmentioning
confidence: 82%
“…Paradoxically, activation of ERK1/2, which also is upregulated by insulin (Gosmanov et al 2002) and promotes mTOR activity and protein synthesis in skeletal muscle (Mccubrey et al 2011), was augmented in LD and gastrocnemius between day 9 and 21 across all groups. Although speculative, this effect may be a consequence of the developmental increase in postprandial insulin levels observed in the study (data not shown), as well as an increase in muscle activity (Gosmanov et al 2002) associated with piglet growth (Brown et al 2015). …”
Section: Discussionmentioning
confidence: 82%
“…It is generally known that the frequency of play declines with reduced nutrient intake in a variety of animals (Duve et al, 2012;Krachun et al, 2010;Reale & Bousses, 1999). Similarly, Brown, Klaffenbock, Nevison, and Lawrence (2015) reported that growth rates in postnatal piglets were significantly and positively associated with play behavior. Our result that indicated there was a significant relationship between the frequency of locomotor play (galloping, leaping, and turning) and growth rate is consistent with the Surplus Resource Theory on play behavior coined by Burghardt (1988).…”
Section: Discussionmentioning
confidence: 97%
“…The observer used a 10 second window to aid in accurate identification of the behaviour occurring at the start of every scan sample. A condensed ethogram based on previous work in enrichment (43) and play (44) in pigs (Table 1) was used. All behaviours were recorded as frequencies.…”
Section: Methodsmentioning
confidence: 99%